(untitled) (International Journal of Engineering and Computer Science, 2017)
Sensors are the physical devices whose function is to sense/detect the changes around its environment, and provides a corresponding output. There are differenct types of sendors available which are used for discrete applications. A Biosensor is a device used to detect nutrients (protein, vitamin etc) or chemicals (antioxidants, carbon contents etc). This paper presents the idea of making a costeffective device using sensors to detect nutrient, chemical contents in foods like vegetables fruits etc and the output of these must be displayed in smart phones.